The pay and conditions debate: the reality of the working environment in midwifery higher education. - Chenery-Morris, Sam; Divers, Jo (British Journal of Midwifery, 2024)
This series of six articles is inspired by themes arising from the Royal College of Midwives' state of midwifery education report. The series explores the current landscape and challenges in educating the future midwifery workforce, particularly those that relate to the higher education workforce. This fourth article looks at what it is like to work in midwifery education compared to in practice as a midwife. The challenges associated with transition, remuneration, workload, casual working and the breadth of the midwifery education role are examined, particularly in comparison to other disciplines in higher education. The article explores how educators can be better supported in their training of the future midwifery workforce, while assuring their own progression and equal treatment in an increasingly competitive and tightly regulated sector.